Delayed diagnosis of Mycobacterium marinum infection - Dolenc-Voljč, Mateja (Acta dermatovenerologica Alpina, Pannonica et Adriatica, 2010)
Mycobacterium marinum infection is the most common atypical skin mycobacterialinfection of increasing importance. It results from skin injury and contact with contaminated aquarium water, fish, or shellfish; it is only rarely related to swimming pool sources nowadays. Diagnosis should be confirmed by isolation and identification of the organism; however, this gold standard is difficult to achieve in practice. Therefore, the diagnosis is primarily based on clinical examination, histopathology, and response to therapy. Awareness of this infection is still low and diagnosis often delayed,as presented in this case of a young immunocompetent patient with M. marinum infection of a chronic course. The reasons for the delay in diagnosis are discussed and current diagnostic and treatment recommendations are reviewed.
Keywords: Adolescenca; Adolescence; antibiotic; Antibiotics; Antibiotiki; dermatologija; Diagnosis; Drug Therapy; infekcije; Kožne bolezni bakterijske; Mikobakterijske infekcije netipične; mikoze; Mycobacterium Infections, Atypical; Plavalni bazeni; Skin Diseases, Bacterial; Swimming Pools; Treatment Outcome; Zdravljenje, izid